Economic and Social Poverty Determinants in Sudan – Standard Analytical Study for the period (1980- 2019) by using Auto Regressive Distributed Lag Model (ARDL) - فاتور حسن علي عثمان; Musa, Fadul Algheli Elsued; Osman, Ibrahim Yagoub Ismail; Tarig Mohamed Elrsheid Ismail (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to measuring economic and social poverty determinants in Sudan, to achieve this goal a standard model for the relationship between the variables of the study was formulated and constructed during the period 1980 – 2019. The study problem lies in the main question: why poverty is increasing in Sudan although, many programs and tools for reducing poverty have been made by the State? The study assumed some hypotheses, the most important one is existence of inverse relationship having a positive impact statistically between unemployment and poverty in Sudan. The study has concluded that a positive relationship exists between unemployment and poverty, and a negative relationship exists between economic growth and poverty in Sudan. The study concluded of that there is an impact of the independent variables on poverty by a rate of 91%. The Researchers has recommended the necessity of a deflationary monetary policy to control inflation in order to reduce poverty rate.